Benefits of yoga on women with Polycystic Ovarian Syndrome (PCOS) - J P; Harnoor, Sanvi; Malewar, Vanita (International Research Journal of Ayurveda & Yoga, 2024)
Polycystic ovary syndrome (PCOS) is a hormonal imbalance that occurs when the ovaries produce and release eggs creating excess hormones. Affected women range in age from 6% to 20%, depending on the diagnostic criteria. Hyperandrogenism and persistent anovulation are two characteristics of the complex condition known as polycystic ovarian syndrome (PCOS). Treatment for PCOS involves lifestyle modifications, education, and symptom-specific therapies for both individuals at risk and those with a confirmed diagnosis. Exercise and dietary changes have long been seen as the cornerstones of managing lifestyle diseases. Yoga is an age-old discipline that aims to balance a person’s mental, emotional, physical, and spiritual aspects. Yoga can improve one’s physical and mental well-being, making them feel better overall. Several research studies have demonstrated the beneficial effects of yoga in PCOS control. Regular yoga practice has been demonstrated to ease the symptoms of PCOS and decrease testosterone levels, also promoting relaxation. The present paper is intended to bring a thematic insight into the problem related to PCOD and the impact of yoga among the patients of PCOD.